Desensitization of the insulin receptor by antireceptor antibodies in vivo is blocked by treatment of mice with beta-adrenergic agonists. - D Elias; M Rapoport; I R Cohen; Y Shechter (The Journal of Clinical Investigation, 1988)
In previous studies we reported that immunization of mice with ungulate insulins induced the development of antiinsulin antibodies, which include an idiotype that appeared to recognize the part of the insulin molecule recognized by the hormone receptor. The antiinsulin antibodies of this idiotype were replaced spontaneously by antiidiotypic antibodies. The antiidiotypic antibodies, which persisted for about 14 d, mimicked insulin and functioned as antibodies to the insulin receptor. They induced down regulation, desensitization and refractoriness of the insulin receptor and disturbances in glucose homeostasis in vivo (Shechter, Y., D. Elias, R. Maron, and I.R. Cohen., 1984; Elias, D., R. Maron, I.R. Cohen, and Y. Shechter. 1984, J. Biol. Chem. 259: 6411-6419). We now report that effects of the antiidiotypic antibodies on the insulin receptor effector system can be modified pharmacologically. Administration of the beta-adrenergic agonist isoproterenol during the period of insulin resistance (days 26-40 after primary immunization), largely restored fat cell responsiveness to insulin, and eliminated the appearance of fasting hyperglycemia. This restoration appeared to be caused by inhibition of both insulin receptor desensitization and refractoriness. In contrast, down regulation of insulin receptors was not reversed by isoproterenol treatment in vivo. The effects of treatment with isoproterenol persisted for 2-4 d after termination of treatment. The beta-antagonist, propranolol and more so, the beta 1a-antagonist metoprolol, specifically blocked the effect of isoproterenol at a molar ratio of 3-10:1. Oral administration of the cAMP phosphodiesterase inhibitor, aminophylline, was also effective in inhibiting the development of desensitization in fat cells. These results indicate that treatment with beta 1-adrenergic agonists in vivo, or other agents that elevate cellular cAMP levels, can inhibit the development of the "postbinding" defects induced by insulin-mimicking, antireceptor antibodies. These observations have both basic and clinical implications.